Internalization of Islamic Religious Education Values in Moral Development of Students in Madrasah - Djuaini, Achmad (Afkaruna: International Journal of Islamic Studies (AIJIS), 2025)
School-aged children are susceptible to negative influences and moral degradation due to a lack of religious understanding and moral values. Education must not only focus on academics but also instill Islamic values as a guide for life. This study aims to examine the implementation of Islamic Religious Education (PAI) values in the moral development of students at MA Darullughah Waddawah Pasuruan. This research used a qualitative approach with interviews, observation, and documentation methods. The results show that the PAI learning plan at MA Darullughah Waddawah integrates character values through the 2013 Curriculum, and values are instilled through five main methods: contextual modeling, value-based project learning, integrated spiritual habituation, experience-based reflective dialogue, and individual spiritual counseling. The success of these methods is evident in the students’ behavioral changes, as they act consistently according to Islamic values without external supervision. The findings also emphasize the importance of collaboration between the school, family, and community. This study contributes by providing a practical model for effective PAI value internalization in madrasahs with unique socio-cultural characteristics.